STUDI PERBANDINGAN PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN RESTORAN CEPAT SAJI - Anwar, Roseline Mannuela (Manajemen Bisnis Kompetensi, 2016)
ABSTRACT Fast food restaurants is an obvious example of the hybrid product which shows the mix of tangible goods and intangible service. In a fast food restaurant, customers not only buy and consume food from the restaurant, but they also getting the services provided by the restaurant. This shows that there is a combination between products (tangible) and services (intangible) in a fast food restaurant industry. Customer satisfaction can be determined by the quality of the products (food) and the services provided by the restaurant. The purpose of this study was to examine the effect of product quality and service quality on customer satisfaction in fast food restaurants mediated by value perception and price perception. In this study, researcher will compare the two models, which is the model of product quality and service quality models. This research is rarely to do, especially comparing two model in marketing research. The non-probability sampling method with convenience sampling technique was used to determine the sample of respondents. At the first step, the full model was tested using Covariance-Based Structural Equation Modelling (CB-SEM) and produced unacceptable goodness of fit indices. However, the statistic test of two separated models shows that the product quality has higher significant effect on customer satisfaction of fast food restaurant mediated by both perceived value and perceived price than the effect of service quality. The study also shows that the perceived value has more important role as mediating variable than the role of perceived price. Keywords: product quality, service quality, value perception, price perception, customer satisfaction.